2022
DOI: 10.1007/s11301-021-00254-5
|View full text |Cite
|
Sign up to set email alerts
|

The cauldron has cooled down: a systematic literature review on home advantage in football during the COVID-19 pandemic from a socio-economic and psychological perspective

Abstract: The phenomenon of home advantage (home bias) is well-analyzed in the scientific literature. But only the COVID-19 pandemic enabled studies on this phenomenon—for the first time in history—on a global scale. Thus, several studies to date examined the effects of empty stadiums by comparing regular matches (with supporters) before the COVID-19 restrictions with so-called ghost games (games without supporters) during the pandemic. To synthesize the existing knowledge and offer an overview regarding the effects of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
22
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 30 publications
(23 citation statements)
references
References 77 publications
1
22
0
Order By: Relevance
“…An overview of the first studies conducted during the pandemic was provided by Lago-Peñas & Gómez-Ruano (2022) , who observed a reduction of both phenomena. This observation was further confirmed in a systematic literature review by Leitner et al (2022) , who identified 26 studies that analyzed the last portion of the 2019–20 season, when all matches were played behind closed doors. Out of these 26 studies, only six did not observe a significant and consistent overall decrease of the home advantage and referee bias in the considered leagues ( Almeida & Werlayne, 2021 ; Benz & Lopez, 2021 ; Krawczyk & Strawinski, 2020 ; Matos et al, 2021 ; Ramchandani & Millar, 2021 ; Wunderlich et al, 2021 ), while the other 20 ones did observe a significant decrease of these phenomena ( Bryson et al, 2021 ; Correia-Oliveira & Andrade-Souza, 2021 ; Cross & Uhrig, 2020 ; Cueva, 2020 ; Dilger & Vischer, 2020 ; Endrich & Gesche, 2020 ; Ferraresi & Gucciardi, 2020 , 2021 ; Fischer & Haucap, 2020 ; Hill & Van Yperen, 2021 ; Jimenez Sanchez & Lavin, 2021 ; Konaka, 2021 ; Leitner & Richlan, 2021a ; Link & Anzer, 2021 ; McCarrick et al, 2021 ; Rovetta & Abate, 2021 ; Santana, Bettega & Dellagrana, 2021 ; Scoppa, 2021 ; Sors et al, 2021 ; Tilp & Thaller, 2020 ).…”
Section: Introductionmentioning
confidence: 59%
See 1 more Smart Citation
“…An overview of the first studies conducted during the pandemic was provided by Lago-Peñas & Gómez-Ruano (2022) , who observed a reduction of both phenomena. This observation was further confirmed in a systematic literature review by Leitner et al (2022) , who identified 26 studies that analyzed the last portion of the 2019–20 season, when all matches were played behind closed doors. Out of these 26 studies, only six did not observe a significant and consistent overall decrease of the home advantage and referee bias in the considered leagues ( Almeida & Werlayne, 2021 ; Benz & Lopez, 2021 ; Krawczyk & Strawinski, 2020 ; Matos et al, 2021 ; Ramchandani & Millar, 2021 ; Wunderlich et al, 2021 ), while the other 20 ones did observe a significant decrease of these phenomena ( Bryson et al, 2021 ; Correia-Oliveira & Andrade-Souza, 2021 ; Cross & Uhrig, 2020 ; Cueva, 2020 ; Dilger & Vischer, 2020 ; Endrich & Gesche, 2020 ; Ferraresi & Gucciardi, 2020 , 2021 ; Fischer & Haucap, 2020 ; Hill & Van Yperen, 2021 ; Jimenez Sanchez & Lavin, 2021 ; Konaka, 2021 ; Leitner & Richlan, 2021a ; Link & Anzer, 2021 ; McCarrick et al, 2021 ; Rovetta & Abate, 2021 ; Santana, Bettega & Dellagrana, 2021 ; Scoppa, 2021 ; Sors et al, 2021 ; Tilp & Thaller, 2020 ).…”
Section: Introductionmentioning
confidence: 59%
“…Considering exclusively the peer-reviewed, multi-leagues studies, they found that nine out of 13 studies observed such a decrease ( Bryson et al, 2021 ; Correia-Oliveira & Andrade-Souza, 2021 ; Ferraresi & Gucciardi, 2021 ; Hill & Van Yperen, 2021 ; Jimenez Sanchez & Lavin, 2021 ; Leitner & Richlan, 2021a ; McCarrick et al, 2021 ; Scoppa, 2021 ; Sors et al, 2021 ). Based on these findings, Leitner et al (2022) conclude that spectators support significantly contributes to determine the outcome of matches in professional football.…”
Section: Introductionmentioning
confidence: 82%
“…To verify the influence of matches without any spectators on HA, researchers have, since 2020, been actively conducting studies to compare the results of matches played in the leagues of various countries between the 2018-2019 season and the 2019-2020 season. The results, supported by most studies, indicate that matches played without spectators caused HA to disappear (For systematic review, see Leitner et al, 2022). For example, McCarrick et al (2021) analyzed data from 15 leagues in 11 countries and reported that HA could no longer be seen in matches with no spectators.…”
Section: Introductionmentioning
confidence: 87%
“…In addition, youth and academy players benefit from VR, as simulations of loud fan chants or in-match pressure situations (e.g., opponents running toward them at a high pace) are designed to prepare them to deal with stressful situations in senior football at an early age. As recently shown, the presence or absence of spectators in a football stadium has substantial effects on the psychological states, behavior, and performance of football players and teams (Leitner & Richlan, 2021a, b;Leitner et al, 2022). This may hold even more true for less experienced and younger players, who therefore might benefit even more from this kind of VR training.…”
Section: Introductionmentioning
confidence: 98%